Malignant mesothelioma as a difficult interdisciplinary problem - Rokicki, Wojciech; Rokicki, Marek; Wojtacha, Jacek; Rydel, Mateusz K. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
The authors of the present report review the etiology and clinical symptoms of malignant pleural mesothelioma (MPM) as well as diagnostic techniques (both radiological and biomarkers) used for its detection. Subsequently, they present methods of multimodal treatment (surgery, chemotherapy, and radiotherapy) recommended by the International Mesothelioma Interest Group (IMIG). Finally, they discuss complications and long-term results associated with these methods of MPM treatment.